A First‐in‐Human Clinical Study With TRV734, an Orally Bioavailable G‐Protein–Biased Ligand at the μ‐Opioid Receptor. Issue 2 (8th July 2019) - James, Ian E.; Skobieranda, Franck; Soergel, David G.; Ramos, Kimberly A.; Ruff, Dennis; Fossler, Michael J.
Abstract: TRV734 is an orally bioavailable G‐protein–biased ligand at the μ‐opioid receptor. In nonclinical studies it was potently analgesic while causing less gastrointestinal dysfunction than morphine, suggesting unique benefits in acute pain management. A 2‐part, first‐in‐human study was conducted with ascending doses of TRV734 to explore its tolerability, pharmacokinetics, and pharmacodynamics in healthy volunteers. TRV734 was well tolerated over the dose range 2 to 250 mg when administered orally. Plasma TRV734 maximum concentration and area under the plasma concentration–time curve generally increased with dose, while time to maximum concentration was similar across doses (0.5–1.3 h). The half‐life increased with dose from 10 mg through 150 mg (0.75–2.28 h) but was similar from 150 mg through 250 mg. Pupil constriction, confirming central nervous system μ‐opioid receptor engagement, correlated with higher plasma TRV734 concentrations; the greatest reductions in pupil diameter occurring between 0 and 4 hours after dosing (–2.9 mm/h, with reduction peaking at 1 hour, and returning to baseline by 8 hours). Following administration of TRV734 125 mg under fasted or fed conditions, there was no significant difference in bioavailability when given as a solution or drug in capsule to fasted subjects. When drug in capsule was given to subjects following a high‐fat meal, absorption was slowed, resulting in decreased peak concentrations, but area under the plasma concentration–time curve was not affected.